Effect of Oral intake of Stevia Leaf Powder on Body Weight – An Experimental study - Faruqi, Amna; Subuctageen, Sikander; Mughal, Irfan Afzal; Parveen, Shahida; Zafar, Tooba; Irfan, Asma (Journal of Rawalpindi Medical College, 2022)
Introduction: The steviol glycosides are found in the stevia leaf. These glycosides possess sweetening properties as well as they have antioxidant, anti-microbial, anti-inflammatory, antihyperglycemic, and anti-hypertensive effects. This study was conducted to find out the effect of Stevia leaf on body weight in obese Sprague Dawley male rats. Materials and Methods: This experimental study was carried out on 90 Sprague Dawley male rats. Group1(normal control) was given a standard diet for the entire study period, while the remaining sixty rats were given a high-fat diet (HFD) for 8 weeks to induce obesity. The obese rats were randomly assigned to group 2 (Obese Control) and Group 3 (obese + Stevia) and given HFD for another 6 weeks. The stevia leaf powder was added to the diet of group 3. Diet intake was noted for all the groups. Rats were weighed on the first day of every week, for six weeks, and then at the end of the study period. Results: Body weights of rats in each group, at the start and end of the 6-week intervention period, when compared, showed a significant increase in group 1 (p=0.001), and group 2 (p = 0.001), while group 3 showed a non-significant increase (p = 0.248). The percentage increase in body weight for groups 1, 2, and 3 was 4.8, 9.3, and 1.1, respectively. Graphically, the weekly increase in average body weights of the three experimental groups showed maximum values for group 2. Conclusions: Stevia leaf possesses weight-reducing effects which may be due to inhibition of appetite, reduction in food intake, and consequent weight loss. Keywords: Obesity, weight loss, Natural non-nutritive sweeteners, Stevia